Comparison Of Inter-Appointment Pain Between Calcium Hydroxide Mixed With Normal Saline And Calcium Hydroxide Mixed With 2% Chlorhexidine During Root Canal Treatment - Lamichhane, Puja; Pathak, Bandana; Khadka, Jwolan (Journal of Society of Surgeons of Nepal, 2023)
Introduction: Pain is one of the major and common symptoms a patient goes through during root canal treatment (RCT). Calcium hydroxide [Ca(OH)2] combined with normal saline (NS) is commonly used as an intracanal medicament against root canal pathogens, but combination of Ca (OH)2 with chlorhexidine (2% CHX) is not routinely used. Aim of this study is to compare the combination of Ca(OH)2 +NS and Ca(OH)2 +2% CHX to reduce the interappointment pain in RCT. Methods: A comparative, prospective, qualitative study was conducted in the Department of Conservative Dentistry and Endodontics, KIST Medical College and Teaching Hospital from September 2022 to March 2023. Total of 60 patients aged 16-70 years were included in the study. Group I received Ca(OH)2+NS and group II received Ca(OH)2 +2% CHX. Pain score was recorded using visual analogue scale (VAS) from baseline to 6,12,24 and 48 hours. Results: The mean pain score after 6 hours for Group I was 0.93(±0.83) and Group II was 1.43 (±0.63); P=0.011. The mean pain score after 12 hours for Group I was 0.40(±0.56) and Group II was 0.90(±0.66); P=0.003. 24 hours, mean pain score for Group I was 0.27(±0.45) and Group II was 0.60(±0.56); P=0.014. Patients reported reduction of pain after 24 hours, with Ca(OH)2 +NS (Group I) than Ca(OH)2 +2% CHX (Group II). Conclusion: The combination of Ca(OH)2 +NS was more effective in reducing interappointment pain than Ca(OH)2 +2%CHX.